Grammatical Errors in Using Tenses Made by ESP Students - Arni Fitri; Nyayu Yayu Suryani (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
Sometimes the students of ESP or Non-English majoring error in using tenses. The low level of students' understanding of tense is one of the factors that greatly influences errors in making sentences. The objective of this research was to describe the students’ errors and its causes in using tenses. In this research, the writers used a qualitative method in a form of descriptive analysis (percentage) that included observation, collecting the students’ test, analyzing, and interpreting the data. For collecting the data, the researcher used test as the instrument. This research was conducted to 35 ESP students of Pharmaceutical Study Program of Institute of Health Science of Siti Khadijah Palembang. The result of the research showed that the percentage of the error made by 35 students as the samples in using tenses was 75%, consisted of the error of selection was 30%, the error of omission was 24% and error of ordering 21%. It means that the students of Pharmaceutical Study Program of Institute of Health Science of Siti Khadijah Palembang made error in using tense, because more than 70% of the students made error. The probable sources of the students’ error were interlanguage error and context in learning error, where 52% errors were caused by interlanguage.